Allobetulin - Mirosława Grymel; Jakub Adamek (Molbank, 2022)
Allobetulin was synthesized at room temperature, starting from betulin by Wagner–Meerwein rearrangement in the presence of tetrafluoroboric acid diethyl ether complex. The structure of the compound obtained was confirmed by spectroscopic methods (1H, 13C NMR and IR).